VALIDITY OF ETHNOSCIENCE BOOKLET MEDIA IN THE REGION OF PONOROGO ON SOUND WAVE SUB MATERIAL - Alsa Vika Zuyina; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This research aims to develop innovative media in the learning of the students in form of ethnoscience booklet in the region of Ponorogo for junior high school students in sub material of sound wave. Ethnoscience media booklet is one of the learning support materials of students that associate the sound wave material with tone alignment technique on traditional music instruments of gong, boning, and saron in Ponorogo. Type of research used is R&D (Research and Development), namely potential analysis and problem stage, data collection, booklet design, media validation, and media revision. Instrument validation of media ethnoscience booklet uses material validation sheets and media validation sheets of ethnoscience booklet. The material validation sheets of ethnoscience booklet is assessed of content feasibility, linguistic, presentation technique, and ethnoscience orientation. For a while, the media validation is composed of cover design and content design. The validation result shows the cover design gets 95%, content design gets 96%, content feasibility aspect gets 98%, linguistic 91%, presentation technique 92%, and ethnoscience orientation gets 96%. In this study, it can be concluded that the ethnoscience booklet based on assessment of material expert and media expert with the tendency of criteria is very feasible to be used as learning media.